Are we just engaging 'the usual suspects'? Challenges in and practical strategies for supporting equity and diversity in student–staff partnership initiatives. Issue 2 (17th February 2021) - Mercer-Mapstone, Lucy; Islam, Maisha; Reid, Tamara
ABSTRACT: Higher education institutions have been identified as inequitable for historically marginalised student and staff populations. Student–staff partnership has recently emerged as one approach to redressing such inequities. To what extent are institutional partnership schemes considering or achieving this goal? Using two phases of qualitative data collection, we explored the perceptions of staff administering student–staff partnership schemes regarding the inclusion of diversity across eight UK higher education institutions. Results highlight conceptual and practical challenges for and strategies to striving for equity in student–staff partnership initiatives. These results are discussed by drawing on the identities of the research team to highlight intersectional approaches to inclusion in partnership.